THE INFLUENCE OF ECO-MATERIALS ONFURNITURE AND INTERIOR PRODUCTION IN MACEDONIA - Namicev, Petar; Tasevska, Viktorija (Journal of process management and new technologies, 2018)
The modern style of living very often dictates us to spend great part of our time in a  working atmosphere i.e. in business space with business services, in restaurants, as well as in hotels. That is why it is very important these kinds of environment to be planned in a way that would remind us on a cozy domestic atmosphere. In the interiors, sustainable materials still have the epithet of timeless materials which never go out of fashion. However, the special moment in choosing the material depends on an individual’s lifestyle. Recently, more emphasis is put on the quality and longevity of natural (eco) materials, because not only they are good for people and living environment, but also the same ones are with an unsurpassed quality.  The materials used as their replacement cost less, but their quality is not nearly with the same quality and longevity. The term eco-material represents a term which widely includes natural resources derived directly from nature, and the same ones can be used for various projects in interior design. With the use of natural materials in the home, there is a warm feeling which is also felt in the nature itself. In Macedonia the use of eco -materials is different, depending on the type of production of the furniture manufacturing companies. On the basis on the researches that I made of some Macedonian companies of this type, you will learn what materials, and in what percent and what purpose they are used for.